Conductive material dispersion liquid, negative electrode slurry composition, and negative electrode for secondary battery
By using a conductive material dispersion with high solid content, including SWCNT and MWCNT, in the manufacturing process of the negative electrode for secondary batteries, the problem of difficult dispersion of conductive material powder is solved, and the solid content of the negative electrode and the adhesion and life characteristics of the electrode are improved.
Patent Information
- Application Number
- CN202480004985.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-21
- Filing Date
- 2024-02-08
- Publication Date
- 2025-06-27
AI Technical Summary
When manufacturing the negative electrode for secondary batteries, the powder of the high-performance conductive material is difficult to disperse, resulting in extended process and reduced solid content, which affects the adhesiveness and life characteristics of the electrode.
A conductive material dispersion liquid is developed, including single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs) as conductive materials, dispersants and dispersion media, with a solid content of more than 1.5% by weight to improve the dispersion of the conductive material and the solid content of the negative electrode slurry.
By increasing the solid content of the conductive material dispersion liquid, the conductive material is dispersed excellently, the solid content of the negative electrode slurry is improved, the electrode process productivity is improved, and the electrode adhesion and life characteristics are enhanced.
Smart Images

Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive material dispersion liquid, a negative electrode paste composition, and a negative electrode for a secondary battery. Background Art
[0002] When manufacturing a negative electrode for a secondary battery, a conductive material such as carbon nanotubes (CNT) can be added to a negative electrode paste in powder form. In order to disperse the conductive material powder in the negative electrode paste, a method of applying strong kneading treatment using a planetary disperser mixer or the like in the addition step can be applied. However, in the case of a high-performance conductive material, when added in powder form, it is substantially difficult to disperse, and there is a problem of an extended slurry preparation (mixing) process.
[0003] Therefore, it is necessary to develop a paste composition that can manufacture a negative electrode with excellent processability as a negative electrode paste composition containing a conductive material. Summary of the Invention
[0004] (I) Technical Problems to be Solved
[0005] An object of one aspect of the present invention is to provide a pre-dispersion solution of a conductive material having a high solid content.
[0006] Another object of the present invention is to provide a conductive material dispersion liquid that can improve the dispersibility of the conductive material when added to a negative electrode paste composition.
[0007] Another object of the present invention is to provide a conductive material dispersion liquid that can increase the solid content of the negative electrode paste.
[0008] Another object of the present invention is to provide a paste composition that can manufacture a negative electrode with excellent processability.
[0009] Another object of the present invention is to provide a negative electrode for a secondary battery having improved adhesion between the current collector and the mixture layer.
[0010] Another object of the present invention is to provide a negative electrode for a secondary battery having excellent life characteristics.
[0011] Another object of the present invention is to provide a negative electrode for a secondary battery having a low resistance.
[0012] (II) Technical Solutions
[0013] A conductive material dispersion according to a specific embodiment contains a conductive material, a dispersant, and a dispersion medium. Among them, the conductive material contains single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT), and the solid content of the conductive material dispersion is 1.5 wt% or more.
[0014] The maximum diameter of the conductive material can be 10 nm or more.
[0015] The Raman R value of the conductive material according to the following formula 1 can be 0.01 or more.
[0016] [Formula 1]
[0017] Raman R = I D / I G
[0018] In the formula 1, the I D is the peak intensity value in the absorption region of 1350 - 1380 cm -1 and the I G is the peak intensity value in the absorption region of 1580 - 1600 cm -1 .
[0019] The powder resistance of the conductive material at a compaction density of 1 g / cubic centimeter (g / cc) can be 0.001 Ω·cm or more.
[0020] The content of the conductive material can be 0.5 wt% or more.
[0021] The dispersant can be any one selected from the following: one or more polymer compounds selected from substituted or unsubstituted aliphatic compounds, polysaccharide compounds, and rubber-based compounds; a copolymer copolymerized from one or more of the polymer compounds; and a combination of the polymer compound and the copolymer.
[0022] The weight ratio of the dispersant contained in the conductive material dispersion to the conductive material can be 1 to 10 times.
[0023] The conductive material dispersion can have a shear viscosity of 140 Pa·s or less at a shear rate of 0.1 / second.
[0024] The average value of the 1 Hz phase angle before and after shearing of the conductive material dispersion at a shear rate of 500 / second can be 11° or more.
[0025] A negative electrode paste composition according to a specific embodiment contains the conductive material dispersion described in any one of the above specific embodiments.
[0026] The solid content of the negative electrode paste composition may be 40% by weight or more.
[0027] The negative electrode for a secondary battery according to a specific embodiment is manufactured from the negative electrode paste composition described in any one of the above specific embodiments.
[0028] The negative electrode for a secondary battery may contain a silicon-based active material.
[0029] The silicon-based active material may be selected from Si, SiO x (0 < x < 2), SiO doped with a metal or coated with carbon x (0 < x < 2), Si-C composite, and Si-Q alloy (wherein Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, and Q is not Si), and at least any one of them.
[0030] The electrode adhesion value of the negative electrode for a secondary battery may be 0.035 N / 18 mm or more.
[0031] (III) Beneficial Effects
[0032] According to a specific embodiment of the present invention, a solution in which a conductive material is excellently pre-dispersed can be provided.
[0033] According to another specific embodiment of the present invention, a negative electrode paste composition in which a conductive material is excellently dispersed can be provided.
[0034] According to another specific embodiment of the present invention, aggregation between compositional factors in the negative electrode paste can be suppressed.
[0035] According to another specific embodiment of the present invention, a conductive material dispersion liquid for preparing a negative electrode paste composition having a high solid content characteristic can be provided.
[0036] According to another specific embodiment of the present invention, a negative electrode paste composition having a high solid content can be provided.
[0037] According to another specific embodiment of the present invention, a negative electrode for a secondary battery can be manufactured with excellent processability.
[0038] According to another specific embodiment of the present invention, the adhesion between the current collector and the mixture layer in the negative electrode for a secondary battery can be improved.
[0039] According to another specific embodiment of the present invention, the occurrence of the peeling phenomenon of the mixture layer during battery charging / discharging can be suppressed. Best Mode for Carrying Out the Invention
[0040] Hereinafter, various specific embodiments according to the present invention will be described. However, the embodiments can be modified into various other schemes, and the scope is not limited to the specific embodiments described below. In addition, throughout this specification, a reference to "a specific embodiment" means that the specific features, structures, or characteristics described in connection therewith are included in at least one specific embodiment of the present invention. Therefore, the expression "a specific embodiment" recited throughout this specification does not necessarily refer to the same specific embodiment.
[0041] According to a specific embodiment, a dispersion liquid in which a conductive material is dispersed by a separate dispersion medium can be used, and the conductive material is added to the negative electrode paste composition. As described above, when the conductive material is added in the form of a dispersion liquid, the conductive material in powder form can be effectively dispersed. However, when the solid content of the dispersion liquid is low, the solid content of the negative electrode paste to which the dispersion liquid is added may also decrease. In this case, the viscosity, fluidity, etc. of the paste cannot be controlled within an appropriate range, so the productivity of the electrode process may be significantly reduced.
[0042] In addition, when the solid content of the paste is relatively low, the phenomenon of "Binder migration" in which the distribution of electrode components such as binders becomes uneven due to their movement together with the solvent during the drying process may be aggravated. Therefore, the adhesiveness and life performance of the finally manufactured electrode may also be significantly reduced. In particular, in the case of a negative electrode using a silicon-based active material having a relatively large volume expansion rate during the charge / discharge process of the battery as a high-capacity negative electrode active material, the peeling phenomenon between the current collector and the mixture layer during the cell driving process may be further aggravated.
[0043] Therefore, in order to increase the solid content of the negative electrode paste and manufacture a negative electrode that can effectively improve the adhesiveness, life characteristics, etc. of the finally manufactured negative electrode, it is necessary to increase the solid content of the conductive material dispersion liquid. According to a specific embodiment of the present invention, the solid content of the conductive material dispersion liquid can be increased to an excellent level. Hereinafter, specific embodiments of the present invention will be described in detail.
[0044] Conductive material dispersion liquid
[0045] The conductive material dispersion liquid according to a specific embodiment contains a conductive material, a dispersant, and a dispersion medium. The conductive material includes single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT), and the solid content of the conductive material dispersion liquid is 1.5 wt% or more.
[0046] Existing commercial single-walled carbon nanotubes (SWCNTs) are carbon nanotubes (CNTs) composed of only a single-walled structure, which have relatively excellent crystallinity, conductivity, etc. However, the preparation process is complex, so the price is relatively expensive, and it is relatively difficult to disperse using a dispersion medium. Therefore, there are substantial limitations in increasing the solid content of the dispersion. On the other hand, according to a specific embodiment, the conductive material dispersion contains both single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs) as conductive materials. Thus, compared with a dispersion containing only single-walled carbon nanotubes (SWCNTs), the economy, solid content, etc. can be increased to a relatively high level.
[0047] The solid content of the conductive material dispersion can be 1.5 wt% or more, specifically 1.7 wt% or more, 2.0 wt% or more, 2.3 wt% or more, 2.5 wt% or more, 2.7 wt% or more, or 3.0 wt% or more, and can be 10 wt% or less, 5 wt% or less, or 4 wt% or less. When the solid content of the conductive material dispersion is within the above range, the dispersibility of the conductive material can be ensured to reach an excellent level, and at the same time, the solid content can be relatively greatly increased. Therefore, the productivity of the electrode process, the electrode adhesion, etc. can be effectively improved.
[0048] According to a specific embodiment, the maximum diameter of the conductive material can be 10 nm or more. Specifically, the maximum diameter of the conductive material can be 15 nm or more, 20 nm or more, or 30 nm or more, and can be less than 50 nm or 40 nm or less. The diameter of the single-walled carbon nanotubes (SWCNTs) can be 0.5 nm to 10 nm, specifically about 1 nm to 5 nm. On the other hand, the maximum diameter of the multi-walled carbon nanotubes (MWCNTs) can be 10 nm or more. The maximum value of the diameters of the conductive materials contained in the measured conductive material dispersion containing both single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs) as conductive materials according to a specific embodiment can be as described above.
[0049] According to a specific embodiment, the average number of walls of the conductive material can be 3 to 10, specifically 5 to 7. The number of walls of the single-walled carbon nanotubes (SWCNTs) can be 1 to 2, and the number of walls of the multi-walled carbon nanotubes (MWCNTs) can be 3 or more. The average number of walls of the conductive materials contained in the conductive material dispersion containing both single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs) as conductive materials according to a specific embodiment can be as described above.
[0050] The Raman R value of the conductive material according to the following formula 1 can be 0.01 or more.
[0051] [Formula 1]
[0052] Raman R = I D / I G
[0053] In the above Formula 1, the I D is the peak intensity value in the absorption region of 1350 - 1380 cm -1 , and the I G is the peak intensity value in the absorption region of 1580 - 1600 cm -1 .
[0054] The Raman R value is a parameter representing the relative crystallinity of a substance. The I D value represents the peak intensity of the region related to the amorphous state, and the I G value represents the peak intensity of the region related to the crystalline state. Therefore, the larger the Raman R value, the relatively lower the crystallinity of the substance; the smaller the Raman R value, the relatively higher the crystallinity of the substance.
[0055] The single-walled carbon nanotube (SWCNT) is a high-density conductive material with relatively excellent crystallinity, conductivity, etc., and has a relatively low Raman R value. On the other hand, the multi-walled carbon nanotube (MWCNT) is a low-density conductive material with excellent dispersibility, etc., and has a relatively high Raman R value. Therefore, when performing Raman spectroscopy analysis on a conductive material containing both the single-walled carbon nanotube (SWCNT) and the multi-walled carbon nanotube (MWCNT), the measured Raman R value calculated according to the above Formula 1 can be relatively larger compared to a conductive material containing only the single-walled carbon nanotube (SWCNT).
[0056] Specifically, when performing Raman spectroscopy analysis on the conductive material containing both the single-walled carbon nanotube (SWCNT) and the multi-walled carbon nanotube (MWCNT), the Raman R value calculated according to the above Formula 1 can be 0.01 or more, more specifically 0.012 or more, and can be 0.1 or less, less than 0.03 or 0.02 or less. When the Raman R value of the conductive material is within the above range, the conductive material can simultaneously have excellent conductivity, dispersibility, etc.
[0057] The Raman R value of the conductive material can be the value measured for light with a wavelength of 532 nm. Specifically, it can be the value calculated according to the above Formula 1 by performing Raman spectroscopy analysis on the CNT powder mixed with SWCNT and MWCNT using light with a wavelength of 532 nm. At this time, the I D value and the I G value are calculated as the sum of the I D values of SWCNT and MWCNT respectively and the I GThe sum of the values, so that the Raman R value can be measured as a single value.
[0058] According to a specific embodiment, the powder resistance of the conductive material at a compaction density of 1 g / cm³ can be 0.001 Ω·cm or less. Specifically, the powder resistance of the conductive material at a compaction density of 1 g / cm³ can be more than 0.001 Ω·cm or 0.0015 Ω·cm or more, and can be 0.04 Ω·cm or less, 0.01 Ω·cm or less, or 0.003 Ω·cm or less. The powder resistance of the conductive material can be a value measured for CNT powder (powder mixed with SWCNT and MWCNT) compressed to a compaction density of 1 g / cm³ using a powder resistance measuring instrument equipped with a four-point probe. When the powder resistance value of the conductive material is within the above range, the conductive material can have excellent conductivity, mechanical strength, etc. within an appropriate range.
[0059] According to a specific embodiment, in the conductive material dispersion, the content of the conductive material can be 0.5 wt% or more. Specifically, the content of the conductive material can be 0.6 wt% or more, 0.8 wt% or more, 1.0 wt% or more, 1.1 wt% or more, or 2.0 wt% or more, and can be 10 wt% or less, 5 wt% or less, or 3 wt% or less. When the content of the conductive material is within the above range, excellent dispersibility of the conductive material can be ensured, and at the same time, the solid content can be increased, thereby improving electrode process productivity, etc.
[0060] According to a specific embodiment, the conductive material can contain single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT) in a weight ratio of 10:90 to 90:10. Specifically, it can contain single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT) in a weight ratio of 20:80 to 70:30. When the content ratio of SWCNT to MWCNT is within the above range, MWCNT can be included within the range that does not hinder the effect of SWCNT, so that the conductivity, dispersibility, etc. of the conductive material can be ensured simultaneously.
[0061] According to a specific embodiment, in addition to single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs), the conductive material dispersion may further include an additional conductive material. The additional conductive material is used to impart conductivity to the electrode and maintain the structure of the electrode, etc. A conductive material that does not cause side reactions with other factors of the secondary battery and has conductivity can be used. Exemplarily, the additional conductive material may include one or more of the following: graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking carbon black, carbon fiber, graphene; metal powders or metal fibers such as copper, nickel, aluminum, silver; conductive whiskers such as zinc oxide, potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives.
[0062] In addition, in addition to the conductive material, the conductive material dispersion may further include a dispersant, and the dispersant may be any one selected from the following: one or more polymer compounds selected from substituted or unsubstituted aliphatic compounds, polysaccharide compounds, and rubber-based compounds; a copolymer copolymerized from one or more of the polymer compounds; and a combination of the polymer compound and the copolymer.
[0063] Specifically, the substituted or unsubstituted aliphatic compound may be polyvinylpyrrolidone (PVP), polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polytetrafluoroethylene (PTFE), polyethylene (PE), polypropylene (PP), or a combination thereof. The polysaccharide compound may be starch, carboxymethyl cellulose (CMC), hydroxypropyl cellulose (HPC), regenerated cellulose, or a combination thereof. The rubber-based compound may be ethylene propylene diene monomer (EPDM), sulfonated EPDM, nitrile rubber, styrene butadiene rubber (SBR), fluororubber, or a combination thereof. More specifically, the dispersant may include polyvinylpyrrolidone (PVP) and carboxymethyl cellulose (CMC). Polyvinylpyrrolidone (PVP) and carboxymethyl cellulose (CMC) are dispersants applicable to water-based conductive material dispersions containing water as a dispersion medium. When the conductive material dispersion contains polyvinylpyrrolidone (PVP) and carboxymethyl cellulose (CMC) as dispersants, it may have a wider range of uses compared to dispersions using other dispersants, and since it contains water as a dispersion medium, its usability as a water-based conductive material dispersion with excellent economy can be very excellent.
[0064] According to a specific embodiment, the weight ratio of the dispersant contained in the conductive material dispersion liquid to the conductive material may be from 1 time to 10 times. Specifically, the weight ratio of the dispersant to the conductive material may be 1.2 times or more or 1.4 times or more, and may be 7 times or less or 3 times or less. When the content ratio of the dispersant to the conductive material is adjusted within the above range, it is possible to prevent the content of the conductive material from becoming too low, so that the conductive material can be effectively dispersed within the range that does not hinder the effect of improving conductivity by adding the conductive material.
[0065] The conductive material dispersion liquid may have a shear viscosity of 140 Pa·s or less at a shear rate of 0.1 / s. Specifically, the conductive material dispersion liquid may have a shear viscosity of 130 Pa·s or less, 120 Pa·s or less, 110 Pa·s or less, or 73 Pa·s or less at a shear rate of 0.1 / s, and may have a shear viscosity of 50 Pa·s or more, 70 Pa·s or more, 80 Pa·s or more, 100 Pa·s or more, or 120 Pa·s or more.
[0066] In addition, the conductive material dispersion liquid may have a shear viscosity of 2.5 Pa·s or less at a shear rate of 10 / s. Specifically, the conductive material dispersion liquid may have a shear viscosity of 2.3 Pa·s or less, 2.0 Pa·s or less, 1.6 Pa·s or less, or 1.4 Pa·s or less at a shear rate of 10 / s, and may have a shear viscosity of 1 Pa·s or more, 1.4 Pa·s or more, 1.6 Pa·s or more, or 2.0 Pa·s or more.
[0067] In addition, the conductive material dispersion liquid may have a shear viscosity of 0.4 Pa·s or less at a shear rate of 100 / s. Specifically, the conductive material dispersion liquid may have a shear viscosity of 0.36 Pa·s or less, 0.3 Pa·s or less, or 0.24 Pa·s or less at a shear rate of 100 / s, and may have a shear viscosity of 0.2 Pa·s or more, 0.24 Pa·s or more, 0.3 Pa·s or more, or 0.36 Pa·s or more.
[0068] In addition, the conductive material dispersion liquid may have a shear viscosity of 0.1 Pa·s or less at a shear rate of 1000 / s. Specifically, the conductive material dispersion liquid may have a shear viscosity of 0.08 Pa·s or less, 0.06 Pa·s or less, or 0.05 Pa·s or less at a shear rate of 1000 / s, and may have a shear viscosity of 0.01 Pa·s or more, 0.05 Pa·s or more, 0.06 Pa·s or more, or 0.08 Pa·s or more.
[0069] The shear viscosity value of the conductive material dispersion liquid according to the shear rate may be a value measured at a temperature of 25 °C.
[0070] When the shear viscosity characteristics of the conductive material dispersion are as described above, although the solid content is high, the viscosity of the conductive material dispersion can be controlled at a relatively low level, and within various shear rate ranges, the conductive material dispersion can have excellent fluidity, processability, etc.
[0071] The average value of the 1 Hz phase angle before and after shearing of the conductive material dispersion at a shear rate of 500 / second can be 11° or more. Specifically, the average value of the 1 Hz phase angle before and after shearing of the conductive material dispersion at a shear rate of 500 / second can be 12° or more, 12.4° or more, 13° or more, or 14° or more, and can be less than 45°, 20° or less, 14° or less, 13° or less, or 12.4° or less.
[0072] In addition, the 1 Hz phase angle of the conductive material dispersion before shearing at a shear rate of 500 / second can be 12° or more, 12.3° or more, 12.6° or more, or 13.1° or more, and can be 45° or less, 20° or less, 13.1° or less, or 12.6° or less.
[0073] In addition, the 1 Hz phase angle of the conductive material dispersion after shearing at a shear rate of 500 / second can be 9° or more, 12° or more, 12.3° or more, 12.8° or more, or 13.9° or more, and can be 45° or less, 20° or less, 13.9° or less, 12.8° or less, 12.3° or less.
[0074] At this time, the shearing conditions can apply the condition of applying shearing for 300 seconds at a shear rate of 500 / second. The phase angle (Phase Angle; PA) is a parameter that can evaluate the viscoelastic properties of the electrode paste and can be calculated according to the following formula 2.
[0075] [Formula 2]
[0076] δ = tan -1 (G" / G')
[0077] In the formula 2, δ is the phase angle (°), G' is the storage modulus value measured at a temperature of 25°C, and G" is the loss modulus value measured at a temperature of 25°C.
[0078] The storage modulus value (G'), loss modulus value (G"), phase angle, etc. can be measured and calculated by means of a Plate&Plate (PP) rheometer measurement method. Specifically, a certain amount of slurry can be placed on the lower plate, and the upper spindle Past can be adjusted to a gap of 0.5 mm, and then the rheology can be measured under the constant temperature condition of 25°C. At this time, an oscillation test before and after shear is performed by applying shear for 300 seconds at a shear rate of 500 / second, and based on this result, the phase angle and G (complex modulus) etc.
[0079] The storage modulus value (G') is a value representing the elastic degree of an object. The larger this value is, the more it exhibits the characteristics of an elastic body with a relatively small degree of deformation under an external force and a large property (restoring force) of storing it. On the other hand, the loss modulus value (G") is a value representing the degree of the liquid property of an object. The larger this value is, the more it exhibits the characteristics of being close to a liquid with a large degree of deformation under an external force and a small degree of losing it (restoring force). Therefore, the larger the G" value is relative to the G' value (i.e., the larger the phase angle (δ) is), the more the object can exhibit characteristics closer to a liquid than a solid.
[0080] Generally, the slurry coating process is carried out by coating the electrode slurry stored in a stirring storage tank on a current collector. When the viscoelastic properties of the slurry are not controlled at an appropriate level, it is difficult to smoothly carry out the coating process, so the processability, productivity, etc. may be greatly reduced. Therefore, when the phase angle characteristics of the conductive material dispersion are within the above range, the load uniformity in the coating process can be improved, and the non-uniformity between the coated part and the uncoated part can be reduced, so defects such as the occurrence of coating gaps can be reduced. Therefore, the electrode manufacturing processability, productivity, etc. of the negative electrode slurry composition can reach an excellent level.
[0081] According to a specific embodiment, the dispersion medium contained in the conductive material dispersion may include water. Specifically, the conductive material dispersion may include water as the dispersion medium, so it can substantially contain no organic solvent. Therefore, side reactions or the generation of gases caused by organic solvents can be effectively prevented. In addition, when the conductive material dispersion is an aqueous conductive material dispersion containing water as the dispersion medium, the price of the dispersion medium is low, so excellent economic efficiency can also be ensured. The content of the dispersion medium is not particularly limited, and considering the content of the above-mentioned conductive material and dispersant, the dispersion medium can be included as the balance.
[0082] Negative electrode slurry composition
[0083] According to one specific embodiment, the negative electrode paste composition contains the conductive material dispersion liquid described in any one of the above specific embodiments. Specifically, the negative electrode paste composition may contain the conductive material dispersion liquid described in any one of the above specific embodiments, a negative electrode active material, and a solvent. The negative electrode paste composition contains a conductive material dispersion liquid having a relatively high solid content, so the components in the paste can have excellent dispersibility, and can have excellent fluidity, viscosity characteristics, high solid content characteristics, etc. The detailed description of the conductive material dispersion liquid is repeated with the above content, so the description is omitted.
[0084] The negative electrode active material may contain a silicon-based active material. Due to the relatively high capacity characteristics, the silicon-based active material can increase the energy density of the negative electrode, but the degree of volume expansion / contraction during the charge / discharge process of the battery is relatively large, so the adhesion and life characteristics of the negative electrode may be reduced. In this regard, when the negative electrode paste composition contains a silicon-based active material as the negative electrode active material and also contains the above conductive material dispersion liquid, it can alleviate the reduction of the adhesion of the negative electrode caused by the silicon-based active material, etc., and at the same time, a negative electrode with high capacity characteristics can be manufactured. Therefore, the negative electrode paste composition can have very excellent usability for an Si-based negative electrode containing a silicon-based active material.
[0085] When the negative electrode paste composition contains a silicon-based active material, based on the total solid content of the negative electrode paste composition, the content of the silicon-based active material may be 0.1-50% by weight, specifically 10-30% by weight.
[0086] The type of the silicon-based active material is not particularly limited. Exemplarily, the silicon-based active material may be selected from Si, SiO x (0 < x < 2), SiO doped with a metal or coated with carbon x (0 < x < 2), Si-C composite, and Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, and Q is not Si), and at least any one of them.
[0087] The negative electrode active material may further include a carbon-based active material. Based on the total solid content of the negative electrode paste composition, the content of the carbon-based active material may be 50-99% by weight, specifically 70-90% by weight. The type of the carbon-based active material is not particularly limited. Exemplarily, the carbon-based active material may be appropriately selected from artificial graphite, natural graphite, hard carbon, soft carbon, carbon black, acetylene black, Ketjen black, Super P, graphene, fibrous carbon, and combinations thereof.
[0088] In the negative electrode paste composition containing the conductive material dispersion liquid according to any one of the above specific embodiments, based on the total solid content of the negative electrode paste composition, the content of the conductive material may be 0.01-5% by weight, specifically 0.05-0.3% by weight. In addition, in the negative electrode paste composition, the content of the dispersant may be 0.015-6.5% by weight, specifically 0.065-0.45% by weight.
[0089] The negative electrode paste composition may further include a binder. The binder is not particularly limited as long as it functions to well adhere the components within the negative electrode mixture layer to each other and well adhere the negative electrode mixture layer to the current collector. Exemplarily, the binder may be at least one rubber-based binder selected from styrene-butadiene rubber (SBR), fluorine-based rubber, ethylene-propylene rubber, butyl acrylate rubber, butadiene rubber, isoprene rubber, acrylonitrile rubber, acrylic-based rubber, and silyl rubber; water-soluble cellulose-based binders such as carboxymethyl cellulose (CMC), hydroxypropyl methyl cellulose, methyl cellulose, or alkali metal salts thereof; water-soluble polymer-based binders such as polyacrylic acid (PAA)-based binders, polyvinyl alcohol (PVA)-based binders, and polyvinyl alcohol-polyacrylic acid copolymer (PVA-PAA Copolymer)-based binders; and combinations thereof. Specifically, the binder may include styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), and combinations thereof.
[0090] At this time, the carboxymethyl cellulose (CMC) that may be included as the binder may be the same as or different from the carboxymethyl cellulose (CMC) that may be included as the dispersant. When the carboxymethyl cellulose (CMC) that may be included as the binder is different from the carboxymethyl cellulose (CMC) that may be included as the dispersant, the carboxymethyl cellulose (CMC) that may be included as the binder may have relatively high molecular weight characteristics, and the number average molecular weight (M n ) of the carboxymethyl cellulose (CMC) that may be included as the dispersant may have relatively low molecular weight characteristics.
[0091] Specifically, the number average molecular weight (M of the carboxymethyl cellulose (CMC) that may be included as the dispersantn ) may be greater than or equal to the number average molecular weight (M n ) of the carboxymethyl cellulose (CMC) that can be included as the binder. According to a specific embodiment, the number average molecular weight (M n ) of the carboxymethyl cellulose (CMC) that can be included as the dispersant may be 100,000 - 1,000,000 g / mol, and the number average molecular weight (M n ) of the carboxymethyl cellulose (CMC) that can be included as the binder may be 1,000 - 200,000 g / mol. When adjusting the number average molecular weight (M n ) characteristics of the carboxymethyl cellulose (CMC) that can be included as the dispersant and the carboxymethyl cellulose (CMC) that can be included as the binder as described above, the effects brought by adding the dispersant and the binder can be further improved.
[0092] When the negative electrode paste composition further includes a binder, based on the total solid content of the negative electrode paste composition, the content of the binder may be 1 - 10 wt%, specifically 3 - 5 wt%.
[0093] When the negative electrode paste composition includes styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) as the binder, based on the total solid content of the negative electrode paste composition, the content of the styrene-butadiene rubber (SBR) may be 0.3 - 7 wt%, specifically 1.5 - 3.5 wt%, and based on the total solid content of the negative electrode paste composition, the content of the carboxymethyl cellulose (CMC) may be 0.1 - 5 wt%, specifically 1 - 3 wt%. In addition, the content of the styrene-butadiene rubber (SBR) included in the negative electrode paste composition may be greater than the content of the carboxymethyl cellulose (CMC), and the weight ratio may be 1.1 to 5, specifically 1.3 to 2.
[0094] When the binder-related characteristics of the negative electrode paste composition are as described above, by adjusting the content of the binder to an appropriate range, an increase in resistance can be alleviated, and at the same time, adhesion can be improved.
[0095] The solid content of the negative electrode paste composition may be 40 wt% or more. Specifically, the solid content of the negative electrode paste composition may be 43 wt% or more, 45 wt% or more, 45.5 wt% or more, or 45.9 wt% or more, and may be 70 wt% or less or 50 wt% or less. When the solid content of the negative electrode paste composition is within the above range, the fluidity of the paste is relatively excellent, thereby effectively improving the coating / drying processability and productivity, and alleviating the occurrence of the binder migration phenomenon, thereby enabling the production of a negative electrode having excellent characteristics such as adhesion.
[0096] The method for preparing the negative electrode paste composition is not particularly limited. Exemplarily, the negative electrode paste composition can be prepared by mixing the conductive material dispersion liquid, negative electrode active material, binder, organic solvent, etc. using a Thinky mixer, mechanical stirrer, etc. At this time, exemplarily, the temperature condition of the mixing process can be 20 - 60 °C, exemplarily, the mixing (stirring) speed can be 100 - 2000 RPM or 500 - 1500 RPM, and the mixing time can be 10 - 30 minutes or 4 hours or less.
[0097] Negative electrode for secondary battery
[0098] The negative electrode for secondary battery according to a specific embodiment is manufactured from the negative electrode paste composition described in any one of the above specific embodiments. The negative electrode for secondary battery includes: a negative electrode current collector; and a negative electrode mixture layer formed on at least one surface of the negative electrode current collector. The method for manufacturing the negative electrode for secondary battery from the negative electrode paste composition is not particularly limited, and a conventional manufacturing method can be applied. Exemplarily, the negative electrode for secondary battery can be manufactured by coating the negative electrode paste composition on the negative electrode current collector and drying and calendering it to form a negative electrode mixture layer.
[0099] The type, thickness, etc. of the negative electrode current collector are not particularly limited, and the negative electrode current collector can be appropriately selected from copper foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper, polymer substrates coated with conductive metals, and combinations thereof.
[0100] The negative electrode for secondary battery may contain a silicon-based active material. The type of the silicon-based active material is not particularly limited, but exemplarily, the silicon-based active material can be selected from Si, SiO x (0 < x < 2), SiO doped with metal or coated with carbon x (0 < x < 2), Si-C composite, and Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, and Q is not Si), at least any one of them.
[0101] The electrode body resistance value of the negative electrode for the secondary battery may be 0.04 Ω·cm or less. Specifically, the electrode resistance value of the negative electrode for the secondary battery may be 0.035 Ω·cm or less or 0.03 Ω·cm or less, and may be 0.01 Ω·cm or more or 0.02 Ω·cm or more. In addition, the electrode interface resistance value of the negative electrode for the secondary battery may be 0.02 Ω·cm or less. Specifically, the electrode resistance value of the negative electrode for the secondary battery may be 0.017 Ω·cm or less or 0.016 Ω·cm or less, and may be 0.01 Ω·cm or more. The electrode resistance characteristics can be measured by bringing the four-point probe of an electrode resistance measuring instrument into contact with the negative electrode.
[0102] The electrode adhesion value of the negative electrode for the secondary battery may be 0.035 N / 18 mm or more. Specifically, the electrode adhesion value of the negative electrode for the secondary battery may be 0.04 N / 18 mm or more, 0.043 N / 18 mm or more, or 0.045 N / 18 mm or more, and may be 5 N / 18 mm or less or 1 N / 18 mm or less. The electrode adhesion value can be measured by a method of performing a 90-degree peel test using a peel tester to measure the adhesion between the negative electrode current collector and the negative electrode mixture layer.
[0103] Lithium secondary battery
[0104] The lithium secondary battery according to a specific embodiment includes the negative electrode for the secondary battery described in any one of the above specific embodiments. Specifically, the lithium secondary battery may include the negative electrode for the secondary battery manufactured from the negative electrode paste composition described in any one of the above specific embodiments. Exemplarily, the lithium secondary battery may include the negative electrode for the secondary battery, a positive electrode, and an electrolyte described in any one of the above specific embodiments, and may optionally further include a separator or not include a separator as needed. The detailed description of the negative electrode for the secondary battery is repeated with the above content, and thus the description is omitted.
[0105] There is no particular limitation on the type of the positive electrode active material contained in the positive electrode paste composition. Exemplarily, the positive electrode active material may include one or more of the following: an LCO-based positive electrode active material represented by the chemical formula LiCoO2; a chemical formula Li x Ni a Co b Mn c O y (0 < x ≤ 1.1, 2 ≤ y ≤ 2.02, 0 < a < 1, 0 < b < 1, 0 < c < 1, 0 < a + b + c ≤ 1) represents an NCM-based positive electrode active material; a chemical formula Li 14 Ti 15 O 12The LTO-based cathode active material represented; or the lithium iron phosphate (LFP)-based active material represented by the chemical formula LiFePO4.
[0106] The composition of the electrolyte is not particularly limited, and the electrolyte can be a conventional electrolyte for secondary batteries. Exemplarily, the electrolyte can include one or more of organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc.
[0107] When the lithium secondary battery further includes a separator, there are no particular limitations on the material and structure of the separator, and the separator can be a conventional separator for secondary batteries. Exemplarily, as the separator, the following substances can be applied in a single-layer structure or a multi-layer structure: porous polymer membranes made of polyolefin-based polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers; conventional porous non-woven fabrics formed of high-melting-point glass fibers, polyethylene terephthalate fibers, etc.; and coated separators containing ceramic components or polymer substances. Detailed implementation modes
[0108] Examples
[0109] 1. Carbon nanotubes (CNT) and conductive material dispersion (CNT paste)
[0110] Prepare the conductive material dispersions of Examples 1 to 4 that use different contents of carbon nanotubes (CNT) and dispersants. The conductive material dispersion is a carbon nanotube paste containing 30-70 wt% of single-walled carbon nanotubes (SWCNT) as the conductive material and the balance of multi-walled carbon nanotubes (MWCNT), polyvinylpyrrolidone (PVP) and carboxymethyl cellulose (CMC) as the dispersants, and water as the balance of the dispersion medium. In addition, as the conductive material dispersion of Comparative Example 1, prepare a carbon nanotube paste containing only single-walled carbon nanotubes (SWCNT) as the conductive material. The physical properties of CNTs, the content of CNTs, the content of dispersants, the physical properties of the conductive material dispersion (carbon nanotube paste), etc. of Examples 1 to 4 and Comparative Example 1 thus prepared are shown in Table 1 below. At this time, the content of CNTs refers to the sum of the contents of single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT), and the content of dispersants refers to the sum of the content of polyvinylpyrrolidone (PVP) and the content of carboxymethyl cellulose (CMC).
[0111] In addition, perform Raman spectroscopy analysis on the CNT powder mixed with SWCNT and MWCNT using light with a wavelength of 532 nm, and calculate the CNT Raman R value according to the following formula 1. At this time, the I of CNTD Value and I G The value is calculated as the I of SWCNT and MWCNT respectively D Sum of values and I G Sum of values, so that the Raman R value is measured as a single value.
[0112] [Equation 1]
[0113] Raman R = I D / I G
[0114] In the said Equation 1, the I D is the peak intensity value of the absorption region at 1350 - 1380 cm -1 and the I G is the peak intensity value of the absorption region at 1580 - 1600 cm -1 of the absorption region.
[0115] In addition, for the CNT powder resistance, the CNT powder (powder mixed with SWCNT and MWCNT) with a compacted density compressed to 1 g / cm³ is measured using a powder resistance measuring instrument equipped with a four-point probe; at a temperature of 25 °C, the shear viscosity of the conductive material dispersion (carbon nanotube paste) is measured respectively according to the shear rates shown in Table 1 below; under the condition of applying shear for 300 seconds at a shear rate of 500 / second, the phase angle is measured and calculated by the measurement method of a plate / plate (PP) rheometer. Specifically, a certain amount of slurry is placed on the lower plate, and the upper rotor Past is adjusted to a gap of 0.5 mm, then the rheology is measured under the constant temperature condition of 25 °C, and an oscillation test before and after shear is performed by applying shear for 300 seconds at a shear rate of 500 / second, and the phase angle is measured and confirmed according to the result.
[0116] [Table 1]
[0117]
[0118] Referring to Table 1, in the case of Comparative Example 1 where only single-walled carbon nanotubes (SWCNT) are included as the conductive material, i.e., carbon nanotubes (CNT), different from Examples 1 to 4 which contain both single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT), the maximum diameter of the CNT is less than 10 nm, the CNT Raman value is less than 0.01, and the CNT powder resistance value is below 0.001 Ω·cm.
[0119] In addition, in the case of the conductive material dispersion (carbon nanotube paste) prepared in Comparative Example 1 with a relatively low solid content (less than 1.5 wt%), compared with the conductive material dispersions of Examples 1 to 4, the shear viscosity value is relatively high and the phase angle value is relatively low.
[0120] Considering the above results, in the case of the conductive material dispersion according to Comparative Example 1, compared with Examples 1 to 4, it has a relatively low solid content, high viscosity, low fluidity, etc., so it is judged that the productivity, processability, etc. of the electrode process will be poor.
[0121] 2. Slurry Composition, Negative Electrode, and Secondary Battery
[0122] 1) Negative Electrode Slurry Composition
[0123] The conductive material dispersion prepared as described above was added to a composition containing a carbon-based active material (graphite-based active material), a silicon-based active material (SiC composite), a rubber-based binder (styrene-butadiene rubber (SBR)), and a water-soluble binder (carboxymethyl cellulose (CMC); number average molecular weight (M n ) : 800000 g / mol) to prepare negative electrode slurry compositions according to Examples 1 to 4 and Comparative Example 1, respectively. The composition of the prepared negative electrode slurry composition (the content of each component is based on the solid content) and the total solid content of the slurry are shown in Table 2 below.
[0124] 2) Negative Electrode for Secondary Battery and Lithium Secondary Battery
[0125] The negative electrode slurry composition prepared as described above was coated on a negative electrode current collector (copper foil (Cu-Foil)) with a thickness of 8 μm at a loading weight (LW) of 10.6 mg / cm 2 , and then dried at 120 °C and rolled to a thickness of 134 μm to manufacture a negative electrode for a secondary battery including a negative electrode current collector and a negative electrode mixture layer formed on one surface of the negative electrode current collector (loading weight (LW) after rolling: 10.6 mg / cm 2 , electrode density: 1.68 g / cubic centimeter).
[0126] After that, a positive electrode slurry composition containing an NCM-based active material as a Li-transition metal composite oxide was coated on a positive electrode current collector (aluminum foil (Al-Foil)) and dried to manufacture a positive electrode. A polyolefin separator was provided between the negative electrode and the positive electrode to manufacture a secondary battery cell. Then, the manufactured cell was placed in a soft package for a secondary battery and injected with an electrolyte, which is an electrolyte in which 1 M of LiPF6 is dissolved in a solvent mixed with ethylene carbonate (EC) and dimethyl carbonate (DMC), and then sealed to manufacture a soft package type lithium secondary battery. The manufactured soft package type lithium secondary battery was used as the secondary battery sample for Examples and Comparative Examples.
[0127] 3) Property Evaluation
[0128] (1) Electrode Resistance Characteristics
[0129] The obtained negative electrode was brought into contact with the four-point probe of an electrode resistance measuring instrument (HIOKI Co., Ltd.), and the bulk resistance value and the interfacial resistance value of the negative electrode were measured respectively, and the results are shown in Table 2 below.
[0130] (2) Electrode adhesion
[0131] A 90-degree peeling test was performed on the obtained negative electrode using a peeling tester to measure the adhesion between the negative electrode current collector and the negative electrode mixture layer, and the results are shown in Table 2 below. Specifically, the negative electrode was cut into a size of 18 mm in width and 150 mm in length, and then a tape with a width of 18 mm was pasted on the negative electrode current collector, and it was sufficiently adhered using a roller with a load of 2 kg. Then, the negative electrode mixture layer was adhered to one side of a tensile testing machine (IMADA Co., Ltd., DS2-50N) using double-sided tape, and then the tape pasted on the negative electrode current collector was fixed to the other side of the tensile testing machine and the adhesion was measured.
[0132] (3) Capacity retention rate
[0133] The obtained secondary battery sample was subjected to 200 cycles. Herein, one cycle was the following process: charging at 0.3C to the voltage corresponding to SOC 98% under constant current / constant voltage (CC / CV) conditions and then cutting off at 0.05C, and then discharging at 0.3C to the voltage corresponding to SOC 4% under constant current (CC) conditions; then the discharge capacity retention rate relative to the initial discharge capacity was calculated as a percentage (%) and the results are shown in Table 2 below.
[0134] [Table 2]
[0135]
[0136] Referring to Table 2, in the case of the negative electrode paste composition of Comparative Example 1 containing a conductive material dispersion with a relatively low solid content, even under the same conditions, compared with Examples 1 to 4, the solid content of the paste is relatively low, and the adhesion of the finally obtained negative electrode is poor.
[0137] On the other hand, in the case of the paste compositions of Examples 1 to 4 in which the solid content of the paste is relatively high due to the inclusion of a conductive material dispersion with a relatively high solid content, the adhesion of the finally obtained negative electrode is relatively excellent, and the resistance characteristics and life characteristics are also excellent.
[0138] Therefore, as shown in Examples 1 to 4, when a conductive material dispersion liquid containing both single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT) as a conductive material and having a relatively high solid content is used to prepare a negative electrode paste composition, it is judged that the solid content of the paste can be relatively increased, thereby improving the productivity of the electrode process, and the occurrence of the binder migration phenomenon can be alleviated, thereby effectively improving characteristics such as the electrode adhesion force.
[0139] Industrial Applicability
[0140] As described above, the features of the present invention can be applied to all or part of the conductive material dispersion liquid, the negative electrode paste composition, and the negative electrode for a secondary battery.
Claims
1. A conductive material dispersion comprising a conductive material, a dispersant and a dispersion medium, in, The conductive material comprises single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs), The conductive material dispersion has a solid content of 1.5 wt % or more.
2. The conductive material dispersion according to claim 1, wherein The maximum diameter of the conductive material is greater than 10 nm.
3. The conductive material dispersion according to claim 1, wherein The Raman R value of the conductive material according to the following formula 1 is 0.01 or more, [Formula 1] Laman R=I D / I G In the formula 1, I D 1350-1380cm -1 The peak intensity value of the absorption region, the I G 1580-1600cm -1 The peak intensity value of the absorption region.
4. The conductive material dispersion according to claim 1, wherein The conductive material has a powder resistance of 0.001 Ω·cm or more at a compaction density of 1 g / cubic centimeter.
5. The conductive material dispersion according to claim 1, wherein The content of the conductive material is greater than 0.5 wt %.
6. The conductive material dispersion according to claim 1, wherein The dispersant is any one selected from the following: a polymer compound of one or more selected from substituted or unsubstituted aliphatic compounds, polysaccharide compounds and rubber-based compounds; a copolymer formed by copolymerizing one or more of the polymer compounds; and a combination of the polymer compound and the copolymer.
7. The conductive material dispersion according to claim 1, wherein The weight ratio of the dispersant to the conductive material contained in the conductive material dispersion is 1 to 10 times.
8. The conductive material dispersion according to claim 1, wherein The conductive material dispersion has a shear viscosity of 140 Pa·s or less at a shear rate of 0.1 / s.
9. The conductive material dispersion according to claim 1, wherein The average value of the 1 Hz phase angle of the conductive material dispersion before and after shearing at a shear rate of 500 / sec is 11° or more. 10 . A negative electrode slurry composition comprising the conductive material dispersion according to claim 1 .
11. The negative electrode slurry composition according to claim 10, wherein: The solid content of the negative electrode slurry composition is greater than 40 wt %. 12 . A negative electrode for a secondary battery, produced from the negative electrode slurry composition according to claim 10 .
13. The negative electrode for a secondary battery according to claim 12, wherein: The negative electrode for a secondary battery includes a silicon-based active material.
14. The negative electrode for a secondary battery according to claim 13, wherein The silicon-based active material is at least any one selected from Si, SiO x , SiO doped with metal or coated with carbon x , Si-C composite, and Si-Q alloy, where x in the SiO x is 0 < x < 2, x in the SiO doped with metal or coated with carbon x is 0 < x < 2, Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, and Q is not Si.
15. The negative electrode for a secondary battery according to claim 12, wherein The electrode adhesive force value of the secondary battery negative electrode is 0.035 N / 18 mm or more.